Sustainable Management for Organic Fraction of Metropolitan Strong Waste and Modern Sludge - Divya; Keshrwani, R. S. (Universal Research Reports, 2023)
In order to tackle the environmental problems caused by urban waste management, this research investigates ways to sustainably handle organic fraction of metropolitan solid waste (OFMSW) and municipal sludge. Before discussing the environmental effects and constraints of conventional disposal techniques, we take a look at the existing situation of organic, food-based municipal solid waste (OFMSW) and sludge management. Next, the research explores how OFMSW and sludge may be managed in a sustainable way by looking at concepts such waste reduction, reuse, recycling, and recovery. Sustainable practises may be implemented and reaped in a variety of urban settings, according to a comprehensive review of case studies. To further emphasise their function in improving sustainability, technological advancements in garbage processing and recycling are also investigated. This study goes farther by reviewing applicable rules and regulations, finding loopholes, and offering solutions for better oversight in this field. Problems including limited resources, outdated technology, and a lack of public understanding are addressed. Lastly, the article suggests areas for future research and practise, arguing for better ways to manage municipal sludge and OFMSW via legislation and more integrated, technologically sophisticated methods. This research intends to add to the existing body of knowledge by surveying the state of the art and potential future directions for sustainable urban organic waste management.